The Structural Relationship Model of Talented Management Effecting on Organizational Performance In The Stock Exchange of Thailand - Intharakoed, Marissa; Sansook , Jantana; Rattanapongpinyo, Taninrat (Business Administration and Management Journal Review, 2021)
This article is quantitative research which study in The Stock Market Exchange of Thailand. The objectives are 1) To study the influence of cultural initiative to strategic talent management in organization 2) To study transformational leadership, affect strategic talent management in listed companies 3) To study the impact of strategic talent management on listed companies’ performance 4) To study operational efficiency affect organizational performance. For data collection, 287 listed companies were collected by questionnaires. The respondents were human resource or related managers and senior managers who participating in organizational policy design in companies. The hypothesis testing shows that 1) the cultural initiative influences positively to strategic talent management. 2) the transformational leadership positively affects strategic talent management. 3) the strategic talent management has significant direct effect on organizational performance. 4) the strategic talent management influences positively on operational efficiency. 5) the operational efficiency has direct effect on organizational performance 6) the strategic talent management has significantly indirect effect on organizational performance through the operational efficiency as mediator. The structural equation model of causal factor corresponds to the empirical data.